Alpinia galanga extracts downregulate interleukin-1 β-induced matrix metalloproteinases expression in human synovial fibroblasts - Peraphan Pothacharoen (2018)
Alpinia galanga has been used as alternative medicine for anti-rheumatic activities. However, the precise action of the extract on arthritic diseases is not yet fully understood. In this study, we investigated the effects of A. galanga extracts on the expression of genes involved in catabolic activities in an interleukin-1β (IL-1β)-induced human synovial fibroblast as an inflammatory model. Confluent primary human synovial fibroblasts were treated for 24 h with A. galanga hexane extracts in the presence of recombinant human IL-1β. MMPs in the culture medium were monitored by gelatin zymography. Total RNA was isolated from the cell lysate and analyzed via semiquantitative RT-PCR. After treatment with A. galanga extracts, MMP-2 activity in the culture medium was significantly reduced. In addition, MMP-1, MMP-3, MMP-13, and Cox-2 expression were downregulated. These data suggest that the decrease of gene expression and production of MMPs in synovial fibroblasts against inflammatory stimuli could be due to the effects of the A. galanga extracts. Therefore, A. galanga extracts might be a promising therapeutic agent for arthritis. © The Society for In Vitro Biology 2010.